156k views
5 votes
(x + 2)²
Given: (x + y)² = x² + 2xy + y²

User Myuce
by
6.9k points

2 Answers

5 votes

Answer:

x² +4x +4

Explanation:

Matching the expressions, you see you have y=2. Put 2 where y is and simplify.

(x +2)² = x² +2x(2) +(2)² = x² +4x +4

User Ahhmarr
by
5.6k points
1 vote

ANSWER


{x}^(2) + 4x + 4

EXPLANATION

We want to expand:


(x { + 2)}^(2)

Using the identity:


{( x + y)}^(2) = {x}^(2) + 2xy + {y}^(2)

We put y=2 into the identity to obtain;


{( x + 2)}^(2) = {x}^(2) + 2x(2) + {2}^(2)

This simplifies to:


{( x + 2)}^(2) = {x}^(2) +4x + 4

User Bettsy
by
5.7k points